2020
DOI: 10.1001/jamapsychiatry.2020.0164
|View full text |Cite
|
Sign up to set email alerts
|

Psychotherapy for Depression Across Different Age Groups: A Systematic Review and Meta-analysis

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research. • You may not further distribute the material or use it for any profit-making activity or commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
159
5
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(183 citation statements)
references
References 29 publications
12
159
5
7
Order By: Relevance
“…According to this study, community members' responses improved, mild to significant levels, after MHFA training and substantiated the findings of other researches; evidently patients with mental disorders do not get proper medical care [34][35][36]; exercise helps improvement of mild to moderate anxiety and depression [67][68][69]83]; MH workers should encourage rather than force a patient with mental disorders to seek help in mental health settings [1,[43][44][45][46]; many mental disorders including anxiety disorders, depression and also other disorders improve with non-drug therapies including CBT [39][40][41][52][53][54][55], and remit with antidepressants and anxiolytics [1,50,51]; anxiety and panic disorders do not cause medical diseases but often present with symptoms micking medical diseases [58,59]; strong approval or disapproval of patients aggressive behaviors due to culturally unacceptable lifestyles is against prevailing norms and human rights, and of course prejudiced and stigmatized [1,[43][44][45][46]; exploring non-judgmentally suicidal behavior including indicators of suicide does not increase the risk of suicide rather prevent it [28,[31][32][33][60][61][62]83,84]; immediate discussion and debriefing individuals with acute psychosis due to acute trauma or othe...…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…According to this study, community members' responses improved, mild to significant levels, after MHFA training and substantiated the findings of other researches; evidently patients with mental disorders do not get proper medical care [34][35][36]; exercise helps improvement of mild to moderate anxiety and depression [67][68][69]83]; MH workers should encourage rather than force a patient with mental disorders to seek help in mental health settings [1,[43][44][45][46]; many mental disorders including anxiety disorders, depression and also other disorders improve with non-drug therapies including CBT [39][40][41][52][53][54][55], and remit with antidepressants and anxiolytics [1,50,51]; anxiety and panic disorders do not cause medical diseases but often present with symptoms micking medical diseases [58,59]; strong approval or disapproval of patients aggressive behaviors due to culturally unacceptable lifestyles is against prevailing norms and human rights, and of course prejudiced and stigmatized [1,[43][44][45][46]; exploring non-judgmentally suicidal behavior including indicators of suicide does not increase the risk of suicide rather prevent it [28,[31][32][33][60][61][62]83,84]; immediate discussion and debriefing individuals with acute psychosis due to acute trauma or othe...…”
Section: Discussionmentioning
confidence: 58%
“…Persons in different age groups especially adults/older adults with mild to moderate depression respond to different psychotherapies including interpersonal psychotherapy, cognitive behavior therapy and telephone-delivered psychotherapy fairly well [1,[39][40][41]. However, severe or psychotic depression and bipolar depression needs additional drug interventions including use of antipsychotics, lithium, and antidepressants [42].…”
Section: Participants Responses To 17 Itemsmentioning
confidence: 99%
“…We found that the patients with older age appeared to have a better response to rTMS at 3 weeks. Notably, the link between age and treatment-induced effect in depressed patients has also been highlighted by Cuijpers and colleagues [52]. This meta-analysis found that cognitive behavioral therapy was less effective in children and adolescents rather than adults.…”
Section: Discussionmentioning
confidence: 67%
“…Evidence-based psychotherapies hold clear potential to alleviate mental health problems (Cuijpers et al, 2020;Weisz et al, 2017), yet there is no scientifically-driven consensus for how long treatment should last (treatment duration, including total numbers of hours or weeks a treatment might last) or how often sessions should occur (treatment frequency). In practice, once-weekly therapy is the dominant outpatient service available to youths and adults alike, largely due to long-held beliefs and insurance companies' limiting reimbursable treatment-time to 50-minute, weekly sessions.…”
Section: Retiring Rethinking and Reconstructing The Norm Of Once-wementioning
confidence: 99%